Pengaruh Kualitas Layanan Dan Relationship Marketing Terhadap Loyalitas Nasabah Pada Bank Jatim Cabang Perak Surabaya - Anggia B.P, Feliks; Rachmawati, Nurul Eka; Panjaitan, Hotman (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2016)
This research talked about client loyalty in the East Java Bank of Perak Branch, Surabaya. This research was focused on the enhancement of client loyalty based on the service quality, and relationship marketing. From the testing results on the model in this research, by using random sampling, structural equation model (SEM) analysis, and the assistance of software Amos 20, on 100 respondents, it able to explain the correlation between service quality and relationship marketing on the client loyalty in the East Java Bank of Perak Branch, Surabaya. Results of research showed that 1) Service quality significantly affects the Relationship Marketing. 2) Service quality significantly affects the client loyalty. 3) Relationship Marketing of the East Java Bank of Perak Branch, Surabaya, significantly affects the client loyalty. 4) Service quality significantly affects the client loyalty, indirectly through the relationship marketing of the East Java Bank of Perak Branch, Surabaya. In this research, it was found the Determination Coefficient (RÂ²) of 0.591, this case shows that, with the maximal service, and the good relationship marketing between the bank and the clients will encourage the client loyalty increase of 59.1%. Key words: Service Quality, Relationship Marketing, and Loyalty.